Litsa (Chariklia) Alexandraki (1918-1984) - Anna Amera (Social Work and Society)
Litsa Alexandraki was born in Russia of Greek parents in 1918. Her parents were long established well- to- do Greeks who had to flee Russia due to the political circumstances of the time and come to Greece as refugees. She was educated in Greece and in June 1940 she graduated from the Faculty of Law of Athens University and was assigned as lawyer by the High Court of Greece (Areos Pagos) to the First Instance Court of Athens in August 1941. During the Second World War, Litsa Alexandraki who had also graduated from the School of Voluntary Nurses of the Greek Red Cross, offered her services to the nation and was appointed to high and responsible posts by the Swiss, Greek and International Red Cross.